Trends in the disease burden of cystic echinococcosis in China, 1990–2044 analysis and forecasting study - Jianping Li; Jingjing Wei (Scientific Reports)
Abstract This study aims to analyze changes in the disease burden of cystic echinococcosis in China from 1990 to 2019 and to predict trends from 2020 to 2044. Using the Global Burden of Disease 2019 (GBD 2019) database, we analyzed the trends in annual percentage change (APC) and average annual percentage change (AAPC) for incidence, prevalence, death, and disability-adjusted life years (DALY) rates of cystic echinococcosis in China via the Joinpoint Regression Program 4.8.0.1 software. Additionally, we applied Nordpred modeling to predict future trends in disease burden over the next 25 years. From 1990 to 2019, the incidence and prevalence of cystic echinococcosis in the Chinese population showed an overall increasing trend, whereas the death and DALY rates exhibited an overall decreasing trend. The disease burden of cystic echinococcosis was greater in males than in females, with significant differences across age groups. The highest incidence and prevalence rates were observed in the 10–24 years age group, whereas the lowest occurred in the 0–9 years age group. Fatalities and DALY rates increased with age, particularly in the 70 and older age groups. According to the Nordpred modeling results, the incidence, prevalence, and DALY rates of cystic echinococcosis in China are expected to rise slightly over the next 25 years. The overall disease burden of cystic echinococcosis is projected to increase gradually between 2020 and 2044, with men exhibiting higher incidence, prevalence, and DALY rates than women.